Determination of Normal Skin Elasticity by Using Real‐time Shear Wave Elastography. (25th March 2018) - Yang, Yujia; Wang, Liyun; Yan, Feng; Xiang, Xi; Tang, Yuanjiao; Zhang, Lingyan; Liu, Jibin; Qiu, Li
Abstract : Objectives: To define the reference ranges of normal skin elasticity measurements associated with shear wave elastography (SWE) in healthy volunteers and analyze the factors that may affect SWE. Methods: Mean skin thickness and elastic modulus values from 90 healthy volunteers were evaluated with B‐mode ultrasonography and SWE in the right fingers and forearms, anterior chest, and abdominal walls. Reference ranges of normal skin elasticity were calculated by using lower and upper limits at the 2.5th and 97.5th percentiles. To investigate the effects of potential factors (site, sex, age, body mass index, and skin thickness) on skin elasticity measurements, a 1‐way analysis of variance, the Student t test, and the Pearson correlation test were performed. Results: Skin elasticity was significantly different at different sites ( P  < .05). Mean elastic modulus values were 30.3 kPa for the finger, 14.8 kPa for the forearm, 17.8 kPa for the chest wall, and 9.5 kPa for the abdominal wall, and reference ranges of normal skin elasticity were 12.1 to 48.4kPa for the finger, 3.5 to 26.0 kPa for the forearm, 6.6 to 28.9 kPa for the chest wall, and 3.5 to 15.5 kPa for the abdominal wall. Our study revealed that men had higher skin elasticity measurements than women ( P  < .05), and they were more elevated in participants aged 20 to 50 years than in the other groups at the finger ( P  < .05). The body mass index and skin thickness had a negligible impact on skin elasticity measurements ( P  > .05). Conclusions: This study revealed that the site, sex, and age should be taken into account when determining the reference ranges of normal skin elasticity by skin elasticity measurements.